Generation Contour Lines from Digital Elevation Model (1m) for AL-khamisah, Thi-Qar Government - S. Mahdi, Alaa; K. Mohsin, Musa; M. Hamid, Huda (Iraqi Journal of Science, 2023)
The DEM (Digital elevation model) means that the topography of the earth’s surface (such as; Terrain relief and ocean floors), can be described mathematically by elevations as functions of three positions either in geographical coordinates, (Lat. Long. System) or in rectangular coordinates systems (X, Y, Z). Therefore, a DEM is an array number that represents spatial distributions of terrain characteristics. In this paper, the contour lines with different interval of high-resolution digital elevation model (1m) for AL-khamisah, The Qar Government was obtained. The altitudes ranging is between 1 m – 8.5 m, so characterized by varying heights within a small spatial region because it represents in multiple spots with flat surfaces.